Alleviation of endoplasmic reticulum stress by tauroursodeoxycholic acid delays senescence of mouse ovarian surface epithelium - Vašíčková, Kateřina; Moráň, Lukáš; Gurín, Dominik; Vaňhara, Petr (Cell and tissue research, 2018)
Ovarian surface epithelium (OSE) forms a single layer of mostly cuboidal cells on surface of mammalian ovaries that is inherently exposed to cell stress evoked by tissue damage every ovulation and declines morphologically after menopause. Endoplasmic reticulum (ER) is a principal cell organelle involved in proteosynthesis, but also integrating various stress signals. ER stress evokes a conserved signaling pathway, the unfolded protein response (UPR), leading to cell death or adaptation to stress conditions. In this work, we document that mouse OSE suffers from ER stress during replicative senescence in vitro, develops abnormalities in ER and initiates UPR. Attenuation of ER stress in senescent OSE by tauroursodeoxycholic acid (TUDCA) reconditions ER architecture and leads to delayed onset of senescence. In summary, we show for the first time a mutual molecular link between ER stress response and replicative senescence leading to phenotypic changes of non-malignant ovarian surface epithelium.
Keywords: upregulace; Telomere Shortening; epitel; messenger RNA; Up-Regulation; stárnutí buněk; Down-Regulation; kyselina taurochenodeoxycholová; Female; zvířata; myši; down regulace; Mice; Taurochenodeoxycholic Acid; tunikamycin; RNA, Messenger; Tunicamycin; ženské pohlaví; stres endoplazmatického retikula; Endoplasmic Reticulum Stress; zkracování telomer; Epithelium; ovarium; Cellular Senescence; Animals; Ovary